(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This study determined school climate as predictor of teachers’ job effectiveness in public secondary schools in Anambra State. Three research questions guided the study and three null hypotheses were tested at 0.05 level of significance. The correlational survey research design was adopted for the study. From a population of 7,020 a sample of 1,405 teachers was drawn using stratified random sampling technique. Two questionnaires titled “School Climate Assessment Scale for Teachers” (SCAST) and “Teachers’ Job Effectiveness Scale” (TJES) were used to collect data for the study. The instruments were validated by two experts from the Department of Educational Management and Policy and one expert from the Department of Educational Foundation (Measurement and Evaluation) all in the Faculty of Education, Nnamdi Azikiwe University. Internal consistency of the instruments were determined using Cronbach’s Alpha method and coefficients of 0.75, 0.71, 0.86 were obtained for the three clusters of SCAST while 0.86 was obtained for TJES. Data were analyzed using simple regression analysis for the research questions and p-value was used to determine the significance of prediction at 0.05 significant level. The result among others revealed that open school climate is a strong predictor of teachers’ job effectiveness in public secondary schools in Anambra State, closed school climate is a weak predictor of teachers’ job effectiveness in public secondary schools in Anambra State. Based on the findings, it was recommended among others that the State Ministry of Education should develop handbooks on building and maintaining open school climate to guide principals in shaping the school environment in such a way to facilitate teachers’ job effectiveness, seminars should also be organized by the State Ministry of Education for principals and teachers on how to handle and manage various organizational climate types in schools especially in the areas of closed climates.